A prospective study of prediction of outcomes in perforative peritonitis using apache II scoring system - Singh, Rajinder; Madan, Harprit Kaur; Tayade, Sandeep H. (International Surgery Journal, 2017)
Background: To predict the risk of mortality and morbidity in patients with perforative peritonitis using APACHE II scoring system. To evaluate the usefulness of APACHE II scoring system as a potential clinical and research tool which could be included as routine part of patient assessment in institution like ours. Methods: This was a prospective, observational study of prediction of outcomes in 80 patients of perforative peritonitis using APACHE II scoring system, conducted during the period of 2 years at our tertiary care institute. Results: Predicted death rate of the study was 17.31% and observed death rate was 25%. However, when observed and predicted death rates were compared in group of patients with APACHE II score of <10, it was over estimating the mortality. In group of patients with APACHE II score 11-20 and >20 it was underestimating the mortality. About 71.2% patients came under APACHE II score <10 with mortality of 3.5%. 23.7% came under group of patients with APACHE II score of 11-20 with mortality of 73.6% and only 5% patients had score >20 with 100% mortality were seen amongst them. Conclusions: In the present study, APACHE II scoring system was found to be accurate predictor of group outcome and can be effectively used in prediction of group outcome in similar population, but does not give sufficient confidence for outcome in an individual patient.